Pengaruh Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan Melalui Kompetensi Sumber Daya Manusia (Studi Empiris Pada KSP Kopdit Obor Mas Cabang Utama Sikka) - Santika, Maria; Mitan , Wilhelmina; Romario , Fransiscus De (Universitas Nusa Nipa Maumere, 2025)
This study aims to examine whether human resource competency mediates the influence of accounting information systems on the quality of financial reports at Obor Mas Credit Union, Sikka Main Branch. The study employs a quantitative approach using a survey method. The population consists of all employees at Obor Mas Credit Union, Sikka Main Branch, with a saturated sampling technique, resulting in a sample size of 41 respondents. The data used in this study are quantitative, collected through questionnaires completed by respondents using a Likert scale. Data analysis was conducted using the SPSS (Statistical Package for the Social Sciences) version 2025 software. The findings indicate that human resource competency mediates the relationship between accounting information systems and the quality of financial reports. The Sobel test results show a calculated t-value of 2.100841, which is greater than the critical t-value at a significance level of 0.05, namely 2.0195 (2.100841 > 2.0195).